The American Military After 9/11 - Morgan, M. author. aut Link
IX, 211 p.
Keywords: This book describes the intense mobilization of American society in the Global War on Terrorism coupled with trends in progress before 9/11. With its focus on maximizing civilian casualties, terrorism has been uniquely able to arouse the popular emotion and make us rethink the use of military force.